AI in language teaching, learning, and assessment - Pan, Fang (Hershey, PA : IGI Global, 2024)
'The book focuses on drawbacks of the application of AI in language education, resources available to ensure the ethical and safe academic deployment of AI, and benefits of applying AI through language teaching, learning, and assessment'--
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching -- Computer-assisted instruction; Second language learning -- Computer-assisted instruction; English language -- Study and teaching -- Computer-assisted instruction; English language -- Study and teaching -- Computer-assisted instruction for foreign speakers; Artificial intelligence -- Educational applications